Rights, Symbolism, and Public Policy in Fetal Tissue Transplants - Robertson, John A. (The Hastings Center report, 1988)
The architecture of the fetal tissue transplant controversy is similar to that of many bioethical debates, with a novel twist because of the contested status of the fetus and abortion. Respect for the needs of sick patients appears to conflict with respect for prenatal human life and larger societal concems.